Magneto-Impedansi pada Kumparan Kawat Fe: Hanafi Eko Prasetyo, Utari, dan Budi Purnama - Hanafi Eko Prasetyo, Hanafi Eko Prasetyo; Utari, Utari; Budi Purnama, Budi Purnama (Jurnal Fisika dan Aplikasinya, 2025)
Clarification of magneto-impedance on Fe wire solenoid had reported in this paper. The magneto-impedance phenomenon also had confirmed for both a number solenoid (N), solenoid diameter (d) and wire diameter (D) dependence. The increased for both N and d trigered the reduced of value L. Meanwhile the reduced of L became slow with the increased of wire diameter D. Finally, realization of magneto-impedance respons at low frequency indicated that the phenomenon dominated by magneto-inductive effect.